2022
DOI: 10.1177/15589447211065074
|View full text |Cite
|
Sign up to set email alerts
|

Digital Nerve Management and Neuroma Prevention in Hand Amputations

Abstract: Background: Hand and digit amputations represent a relatively common injury affecting an active patient population. Neuroma formation following amputation at the level of the digital nerve can cause significant disability and lead to revision surgery. One method for managing digital nerves in primary and revision partial hand amputations is to perform interdigital end-to-end nerve coaptations to prevent neuroma formation. Methods: All patients with an amputation at the level of the common or proper digital ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Direct end-to-end neuroanastomosis is technically simpler and clinical studies support its use in human and equine medicine. 17,20,22,23 Despite reported clinical outcomes, histological evaluation has suggested that direct end-to-end anastomosis can increase neuroma formation due to lack of interposition of axon sprouting from each terminal stump. 20,21 In comparison, centrocentral or group fascicular anastomoses have similarly been shown to be both functional and effective at reducing neuroma formation but are both more technically demanding and require significant more dissection when compared to the simpler technique of direct end-to-end anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct end-to-end neuroanastomosis is technically simpler and clinical studies support its use in human and equine medicine. 17,20,22,23 Despite reported clinical outcomes, histological evaluation has suggested that direct end-to-end anastomosis can increase neuroma formation due to lack of interposition of axon sprouting from each terminal stump. 20,21 In comparison, centrocentral or group fascicular anastomoses have similarly been shown to be both functional and effective at reducing neuroma formation but are both more technically demanding and require significant more dissection when compared to the simpler technique of direct end-to-end anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroanastomoses have been described in the human literature as a means to both treat neuroma formation as well as prevent formation thereby improving long-term comfort in patients with digit amputation. 15,17,18 A recent study found that neuroma occurred in 12.8% (10/78 nerves) of cases with end-to-end anastomosis performed compared with 22.7% (48/211 nerves) of cases in which no anastomosis was performed. 17 The main objective of this study was to evaluate the outcome of horses undergoing dorsal-to-palmar branch neuroanastomosis following PDN, including success of the neurectomy as determined by resolution of lameness, postoperative complications, and owner satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative management has proven to be successful in reducing symptoms; however, it is not always sufficient 1,2 . Clinicians should consider surgical intervention in certain situations that are resistant to medicinal treatment 3–5 …”
mentioning
confidence: 99%
“…1,2 Clinicians should consider surgical intervention in certain situations that are resistant to medicinal treatment. [3][4][5] Unlike the central nervous system, the peripheral nerve system (PNS) demonstrates a remarkable capacity to regenerate. 6 It is not clear if cranial nerves follow the PNS model, the central nervous system model, or a different regenerative pathway.…”
mentioning
confidence: 99%